The Failure of R2P and POC in the Case of the Genocide of the Palestinian People by Israel in the Period 2023-2025 - Impiani; Gumilar Sukma, Yusuf; Aepudin, Saepul; Fasa Rahmatulah, Faisal (Candidate: Jurnal Sains Politik, 2025)
The Responsibility to Protect (R2P) and Protection of Civilians (POC) are policies formulated by the United Nations (UN), particularly by the UN Security Council, aimed at preventing and addressing severe crimes against humanity, including genocide, war crimes, and ethnic cleansing. Nevertheless, these two mechanisms were not effectively applied in the instance of genocide faced by the Palestinian people at the hands of Israel during the years 2023 to 2025. This article seeks to explore the reasons behind the unsuccessful implementation of R2P and POC in this scenario. Employing the Causal Process Tracing methodology, researchers will investigate the underlying causes of this failure, ranging from the conceptual dimensions of R2P and POC to the political factors involving the geopolitics of various significant actors. The findings of the study reveal that this failure was significantly shaped by the political supremacy of the permanent members of the Security Council, especially the exercise of veto power by the United States in favor of Israel, which obstructed the formation of an international consensus regarding R2P and POC. These results suggest that the UN, as an international body, lacks the complete authority to enforce R2P and POC, as it remains profoundly affected by political agendas, thereby resulting in a persistent imbalance in the protection of victims of crimes against humanity in Palestine that has endured for many years.